2010
DOI: 10.1007/s11999-010-1271-2
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Bone and Joint Infections in Injecting Drug Abusers

Abstract: Background The literature contains variable reports on the causative organisms of osteomyelitis and septic arthritis in patients with injecting drug abuse and on the rate of oxacillin-resistant S aureus. It is important to have a clear notion of the organisms to initiate empiric antimicrobial therapy. Questions/purposes We therefore determined the spectrum of organisms in bone and joint infections in patients who were injecting drug users. Methods We retrospectively reviewed the medical records of 215 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 16 publications
2
21
0
1
Order By: Relevance
“…In the presence of infection, the local pH decreases leading to the antibiotic release. Using this smart biomaterial, the drug will be released once the infection occurs (immediately after the implantation or months, years later) which limits systemic toxicity, antibiotic resistance and decreasing bioavailability [23,24]. For our study, we have chosen gentamicin sulfate (GS) as antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of infection, the local pH decreases leading to the antibiotic release. Using this smart biomaterial, the drug will be released once the infection occurs (immediately after the implantation or months, years later) which limits systemic toxicity, antibiotic resistance and decreasing bioavailability [23,24]. For our study, we have chosen gentamicin sulfate (GS) as antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…In 1 case series, 73% of intravenous drug users with vertebral osteomyelitis had MRSA. 31 The outcomes in these small case series are about the same (ie, relapse rates , 15%), with a treatment duration of 60 days. 27,33 Vancomycin monotherapy may prove to be an insufficient treatment for vertebral osteomyelitis.…”
Section: Hematogenous Spreadmentioning
confidence: 81%
“…30 The aging population, the increasing use of immunemodulating agents, and intravenous drug use all affect the epidemiology of the disease. 31 Case series of osteomyelitis from the 1990s confirmed S aureus as the most likely organism causing hematogenous spread in adults, and that there is a shift toward more frequent infection in vertebrae than in other bones. 32 Relapse rates in those series were , 15%.…”
Section: Hematogenous Spreadmentioning
confidence: 99%
“…More recently, Allison et al reported on the microbiology of orthopaedic related infections secondary to drug abuse. 23 They reviewed 215 patients over 7 years, and found a high incidence of osteomyelitis (59%) and a predominance of Gram positive bacteria. Wang et al compared the demographics, presentation, treatment and outcomes of surgically treated primary pyogenic infections of the spine between IVDU and non-IVDU patients.…”
Section: Discussionmentioning
confidence: 99%